2021
DOI: 10.3390/app112210932
|View full text |Cite
|
Sign up to set email alerts
|

An Explainable Approach Based on Emotion and Sentiment Features for Detecting People with Mental Disorders on Social Networks

Abstract: Mental disorders are a global problem that widely affects different segments of the population. Diagnosis and treatment are difficult to obtain, as there are not enough specialists on the matter, and mental health is not yet a common topic among the population. The computer science field has proposed some solutions to detect the risk of depression, based on language use and data obtained through social media. These solutions are mainly focused on objective features, such as n-grams and lexicons, which are comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…For future work, we plan to evaluate the performance of PBC4cip [56], a contrast pattern-based classifier that has performed well on tasks such as detecting depressive and xenophobic tweets [57], [58]. Also, compared to popular ML algorithms, it is interpretable, resulting in a set of patterns that provide a deeper understanding of how language is manifested in these mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For future work, we plan to evaluate the performance of PBC4cip [56], a contrast pattern-based classifier that has performed well on tasks such as detecting depressive and xenophobic tweets [57], [58]. Also, compared to popular ML algorithms, it is interpretable, resulting in a set of patterns that provide a deeper understanding of how language is manifested in these mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…They showed KNN was superior with an accuracy of 92%. Authors in Gallegos Salazar et al [42] proposed a contrast pattern-based classifier to detect depression by using a new data representation based only on emotion and sentiment analysis. Similarly, Amanat et al [28] showed RNN-LSTM outperformed SVM, NB, CNN, and decision tress with an accuracy of 99%.…”
Section: Related Workmentioning
confidence: 99%
“…Based on assumptions, the main mechanisms of major depressive disorder include inflammation, disruption, and lack of coordination in hypothalamus function and neurotrophic elements, including neurotrophic factors derived from the brain [4]. Its specific symptoms include loss of energy and interests, low self-confidence, feelings of sadness and guilt, and changes in appetite and sleep patterns, which are associated with differences and similarities in men, women, children, and the elderly, which ultimately reduce the quality of life and the performance of the individuals [5]. One of the important long-term effects of depression is the body's deviation from its normal state.…”
Section: Introductionmentioning
confidence: 99%